Biochar as An Effective Material on Sediment Remediation for Polycyclic Aromatic Hydrocarbons Contamination. (May 2019) - Chen, Z; Chen, J; Yang, X; Chen, C; Huang, S; Luo, H
Abstract: The mechanism of biochar as capping materials on polycyclic aromatic hydrocarbons (PAHs) removal in river sediments was investigated. When biochar was amended, pyrene was decreased through strengthened aging effects (1.6 times), which was attributed to high adsorption capacity of the biochar. While biochar did not alter the main microbial community, it provided a stable niche for PAHs degradation microorganisms, which attributed to the porosity and biological affinity of biochar. According to the results, biochar increased the opportunity for PAH-degraders to contact PAHs in sediments. When electron acceptors were available, the pyrene-degraders in biochar pore degraded the adsorbed pyrene rapidly (+103%). Therefore, biochar could be an effective material on PAHs removal in sediments.